2018
DOI: 10.1029/2017jf004507
|View full text |Cite
|
Sign up to set email alerts
|

On the Link Between External Forcings and Slope Instabilities in the Piton de la Fournaise Summit Crater, Reunion Island

Abstract: We have analyzed the impact of different forcings, such as rain and seismicity, on slope instabilites on an active volcano. For this, we compiled a catalog of the locations and volumes of rockfalls in the Piton de la Fournaise crater using seismic records. We validated it by comparing the locations and volumes to those deduced from photogrammetric data. We analyzed 10,477 rockfalls, spanning the period 2014 to 2016. This period corresponds to the renewal of volcanic activity after a 41‐month rest. Our analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

6
3

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 83 publications
(154 reference statements)
1
35
0
Order By: Relevance
“…The result of this study not only confirm previous observations relating to the combined effect of rainfall and earthquakes on either slow-moving landslides 60 , rapid landslides 17 activity 61 , but also provided quantitative data based on the dv/v which support the previous hypothesis that soil damage causes this combined effect 17 . Soil damage, interpreted as the creation of micro-/macrofractures as a result of earthquake shaking, generates preferential paths for water infiltration and thus impacts landslide motion after an earthquake until the soil has completely healed.…”
Section: Discussionsupporting
confidence: 89%
“…The result of this study not only confirm previous observations relating to the combined effect of rainfall and earthquakes on either slow-moving landslides 60 , rapid landslides 17 activity 61 , but also provided quantitative data based on the dv/v which support the previous hypothesis that soil damage causes this combined effect 17 . Soil damage, interpreted as the creation of micro-/macrofractures as a result of earthquake shaking, generates preferential paths for water infiltration and thus impacts landslide motion after an earthquake until the soil has completely healed.…”
Section: Discussionsupporting
confidence: 89%
“…Over the last two decades, seismic signals generated by granular flows (e.g., landslides, debris flows, and rockfalls) have been investigated increasingly as a useful complementary tool to sparse visual observations, in order to detect flows and deduce informations about their localization and dynamics (e.g., Arattano, 2000;Brodsky et al, 2003;Dammeier et al, 2011;Durand et al, 2018;Huang et al, 2007;Hibert, Ekström, et al, 2017;Hibert, Mangeney, et al, 2017;Kean et al, 2015;Lai et al, 2018;Schöpa et al, 2018;Suriñach et al, 2005;Pérez-Guillén et al, 2016;Yamada et al, 2016;Zhao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Unique strategies for landslide detection, quantification, and monitoring can be designed from seismic data analysis (Chao et al 2017), making it possible to investigate the link between landslide activity and meteorological, climatic, seismic, or volcanic activity. As an example, based on these seismic approaches, Durand et al (2018) showed the stability Seismology and Environment, Fig. 2 (a) The Super Typhoon Ioke in the Pacific ocean from 22 August to 7 September 2006 has been tracked by the National Hurricane Center(blue line), tracks Ioke-generated P wave sources (red) using the Southern California Seismic Network (SCSN).…”
Section: Landslidesmentioning
confidence: 99%